THE ROLE OF EDUCATIONAL ADMINISTRATION IN ENHANCING LEARNING QUALITY: A LITERATURE REVIEW - Khalid, Muhammad; Hidayatullah, Rully (Cahaya Ilmu Bangsa Institute, 2024)
This article explores the critical role of educational administration in enhancing learning quality and institutional success. Through a comprehensive literature review, it examines key functions of educational administration, including leadership, resource management, and technology integration. The findings highlight the significance of transformational and distributed leadership in shaping a positive learning environment and improving student outcomes. Additionally, the article discusses the impact of Educational Management Information Systems (EMIS) and data-driven decision-making on administrative efficiency. The challenges posed by the digital divide and the need for continuous professional development for educational administrators are also addressed. The article concludes with recommendations for policymakers and educational leaders to foster effective administration that adapts to the evolving educational landscape, ultimately driving improvements in learning quality and equity.